Analisis Faktor-Faktor yang Memengaruhi Praktik Perataan Laba (Income Smoothing) pada Industri Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia - B41112089, Irma Nur Fitri Alqadrie (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
ABSTRACT The purpose of this research is to find out whether the profitability of financial risk and size of company has a significant influance income smoothing and leveling practice to determine whether a pratice is often done by companies listed on Indonesian Excanged. This research using quantitative methods where researcher uae test assumptions classic, multiple analysis and tes of hypotesis. The results of this research is first, variable of profitability, financial risk and size of company simultaneously is not significant to income smoothing practice. Second is, variable profitability, financial risk and size of company partially is not significant to income smoothing practice. Key words: Income Smoothing, Profitability, Financial Risk and The Size of Comopany